Transparency of competences via recognition - criteria-based analysis of different European approaches - Annen, Silvia [Verfasser] (My University, 2013)
"The recognition of formal, non-formal and informal learning gains increasing importance in Europe, while the national approaches to recognition are rather diverse [cf. e.g. Otero/Hawley/Nevala 2008; Werquin 2007]. In the European context the professional mobility of the workforce is more in the focus - in the national context aspects like improving permeability of the educational system, support of lifelong learning or employability are focused. Overall the use of the term 'recognition' is in no way consistent [cf. e.g. Käpplinger 2007]. The aim of this paper is an analysis and typology of different European approaches towards the recognition of competences. This is done mostly from an institutional research perspective. Besides the competence theory and the certification theory the theoretical basis of the analysis is formed by the institution theory and the governance approach. Within this paper selected European approaches towards the recognition of competences are analysed criteria-based and on this basis evaluated from a comparative perspective regarding their methodological and their institutional design." (Authors' abstract, BIBB-Doku)
Keywords: L 2.1.1 Informelles Lernen; S 2.2.4.4 Anerkennung non-formaler Qualifikationen; I 2.2 Europa; Kompetenz; Informelles Lernen; Anerkennung; Verfahren; Europa